P531 Stringent screening strategy significantly reduces reactivation rate of Tuberculosis in Patients with Inflammatory Bowel Disease on anti-TNF therapy in a TB endemic region. (21st January 2022) - Kumar, P; Vuyyuru, S K; Kante, B; Sahu, P; Goyal, S; Madhu, D; Jain, S; Ranjan, M K; Mundhra, S; Golla, R; Singh, M; Virmani, S; et al.
Abstract: Background: Anti-tumour necrosis factor (anti-TNF) therapy use in patients with inflammatory bowel disease (IBD) leads to increased risk of tuberculosis (TB) reactivation despite LTB screening, especially in TB endemic regions. We evaluated the effect of stringent screening strategy and latent tuberculosis (LTB) prophylaxis on TB reactivation. Methods: We performed an ambispective comparison between patients who were started on anti-TNF therapy after January 2019 (Cohort A) and between Jan 2005-Dec 2018 (Cohort B). Cohort A patients were subjected to stringent screening criteria which included all: history of past TB/recent contact with active TB, CT (computed tomography) chest, IGRA (interferon-gamma release assay), TST (tuberculin skin test), and if any positive were given chemoprophylaxis. A cohort comparison was done to evaluate for risk reduction of TB following the stringent screening strategy. Results: One hundred seventy-one patients (63-Ulcerative colitis/108-Crohn's disease; mean age diagnosis-28.5±13.4 years; 60% males; median follow-up duration after anti-TNF:33months [interquartile range, 23–57 months]) were included. Among 112 in Cohort B 22(19.6%) had LTB and 19(17%) developed TB. In comparison, 26(44%) had LTB and only 1(1.7%) developed TB in Cohort A (p<0.01). On survival analysis, patients in Cohort B had a higher probability of TB reactivation compared to Cohort A at 5 years of follow up, HR-14.39 (95% CI, 1.88- 109.81[p=0.010]) after adjusting for gender, age at anti-TNF therapy initiation, concomitant immunosuppression, the total number of anti-TNF doses and therapy escalation. *Log rank p value=0.006 Figure 1: Kaplan Meier curve analysis for probability of remaining free from tuberculosis between patients who were started on anti- TNF therapy till January 2019 (Cohort B) and those who were started on anti-TNF after January 2019 (Cohort A). *Log rank p value=0.02 Figure 2: Kaplan Meier curve analysis for probability of remaining free from tuberculosis between patients who had incomplete latent TB screening and those with complete TB screening. Conclusion: The high risk of TB reactivation with anti-TNF therapy in TB endemic regions can be significantly mitigated with stringent LTB screening and chemoprophylaxis.